TEACHER'S EFFORTS IN IMPLEMENTING PEACEFUL LOVE CHARACTER VALUES IN STATE 52 PRIMARY SCHOOL BANDA ACEH - Asyura, Risqa; Husin, M.; Nurmasyitah, Nurmasyitah (Elementary Education Research, 2024)
This research focuses on teachers' efforts to instill the values of peace and character in students at SD Negeri 52 Banda Aceh, with special emphasis on character formation. Character plays an important role in individual interactions in family, school, and society. Character includes knowledge, attitudes, motivation, actions, and skills. Teachers play a very important role in forming positive character traits in students, promoting peace, tolerance and non-violent conflict resolution. This qualitative research uses observation and in-depth interviews to explore how teachers implement and teach the values of peace and character at SD Negeri 52 Banda Aceh. A total of five teachers, principals, and students from grades 4, 5, and 6 were involved as research subjects. This research found that teachers' efforts to implement the character value of peace involve acting as role models, promoting positive behavior, and respecting diversity. They cultivate an environment where peace and harmonious relationships are cultivated. Factors that encourage the implementation of peace character values include teacher example, strengthening positive behavior, and respect for diverse opinions. Teacher integrity and professionalism influence the formation of student character. Their commitment to the profession and interactions with students, parents and colleagues have a significant impact on the development of students' character.